Interventional Response of Hospital and Health Services to the Mental Health Effects of Viral Outbreaks on Health Professionals - Branjerdporn, Grace; Bowman, Candice; Kenworthy, Sean; Stapelberg, Nicolas J. C. (Frontiers in Psychiatry, 2022)
The aim of this integrative review was to examine the impact of past viral epidemics on staff mental health interventional responses, with a specific focus on healthcare provider response in the context of the COVID-19 pandemic. Following PRISMA methodology, databases were searched for relevant articles. A total of 55 articles with a range of methodologies (e.g., commentary papers, cohort studies, qualitative studies) were included to ensure broad coverage of this rapidly emerging research area. The literature showed that many healthcare providers implemented a variety of wellbeing initiatives to support their staff during a viral outbreak. Most of these interventions, however, were not formally evaluated. Interventions included leadership/team support; online psychoeducational resources and updated information on the pandemic; respite spaces; peer support outreach; staff resilience training; telephone hotline support; staff support groups; and individual counselling. Staff were generally supportive of the initiatives offered by hospital and health services, with certain interventions being more appreciated (e.g., staff respite areas). Rapid, locally, and culturally appropriate workplace-based responses may counter the negative mental health impact on staff; but a stepped response is required for a smaller number of staff at risk of mental illness, or those with pre-existing mental illness.